Assessment of Incidence of Aspiration Pneumonia in Infants with Cleft Palate - Taj Muhammad, Farman Ullah, Rida Naz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: A cleft lip (CP) is characterized by a split in upper lip, which may extend into the nose. These abnormal fissures can cause difficulties with nutrition, hearing, speaking and recurrent respiratory and ear infections. Objectives: The study assessed the complications associated with the cleft palate in infants and the incidence of aspiration pneumonia. Methods: The study was conducted in tertiary care hospitals and pediatric clinics at District Dera Ismail Khan, from February 2021 to September 2022, comprising 141 CP patients. Results: The incidence of CP was seen 7.90% in District Dera Ismail Khan, which was higher in males (68.08%) than in females (31.91%). The mean age of the study group was 4.35+3.12, with birth weight and weight at the time of assessment being 3.85+1.78 and 23.78+15.19, respectively. Their mean maternal age and weight at the time of delivery were 32.91+9.07 and 61.65+21.56, respectively. A significant proportion (p<0.05) suffered from aspiration pneumonia (64.53%), while 19.85% of the patients had complained of recurrent pneumonia due to CP. Other complications included chest infection (43.26%), ear infection (8.51%), nasal obstruction (31.91%), vomiting during feeding (26.95%) and regurgitation of milk and other food materials (12.05%). Ten CP patients died (7.09%) due to the complications associated with this disorder. Practical implications: For infants with orofacial clefts, the incidence of LRTIs is potentially high, thus accumulated breastfeeding length might mediate the connections of CP. Conclusion: It was concluded that CP was significantly associated with pulmonary defects and caused fatal LRTIs in the affected population, especially in breastfeeding infants. Keywords: Cleft palate; Ear infections; Fetal defects; Genetic Disorders; Pulmonary infections.